Is there a relationship between back squat depth, ankle flexibility, and Achilles tendon stiffness?. Issue 7 (9th August 2022) - Gomes, João; Neto, Tiago; Vaz, João R.; Schoenfeld, Brad Jon; Freitas, Sandro R.
ABSTRACT: This study investigated the relationship between back squat depth capacity, ankle dorsiflexion resistance to stretch and maximal range of motion (ROM), and Achilles tendon stiffness of healthy individuals (n = 20). Squat depth capacity was assessed with 2D kinematic analysis. Ankle dorsiflexion maximal ROM was assessed using a smartphone digital goniometry (lunge test) and isokinetic dynamometry (prone test). Ankle dorsiflexion resistance to stretch was assessed during the prone test. Achilles tendon stiffness was estimated at rest [using shear wave elastography (stiffness-SWE)] and during isometric contraction through tendon force-length relationship (using B-mode sonography). Squat depth was associated only with ankle dorsiflexion ROM in the lunge test (r = 0.69, p = 0.001). Ankle dorsiflexion ROM in the lunge test was associated with the ankle resistance to stretch (r = 0.46, p = 0.050) and Achilles tendon stiffness-SWE (r = 0.62, p = 0.005); and it was the only variable different between individuals with low and high squat depth capacity (p = 0.014). No other statistically significant associations were found. In conclusion, back squat depth is associated with ankle dorsiflexion ROM when the knee is flexed, without evident influence of global joint and Achilles tendon mechanical properties.